Mental Workload Impact of a Visual Language on Understanding SQL Queries - Silva, Edson A.; Franco, Natália M.; Ferro, Márcio R.; Fidalgo, Robson N. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2019)
Structured Query Language (SQL) is an essential topic in introductory database courses. Despite its declarative syntax, SQL query specification can be confusing. Visual Query Languages (VQLs) are an alternative to reduce this complexity. However, these VQLs do not cover many complex constructions. To overcome this limitation, we present the Diagrammatic SQL (DSQL). Because increased Mental Workload (MW) during task performance may increase fatigue and facilitate errors, our objective is to investigate the MW impact of DSQL on the understanding of SQL queries. In this experiment, we compare the accuracy, time, and ease-of-understanding complex queries using both languages. The results indicate that there is no significant difference.